The effect of preterm birth on the physiological response to exercise testing in school aged children - O'Dea, Christopher Allan (Curtin University, 2020)
An investigation into the impact of preterm birth on the exercise capacity in school-aged children. Children born preterm had decreased lung function and altered lung structure and exhibited an altered ventilatory pattern to exercise characterised by rapid and shallow breathing; however, this did not alter the exercise capacity.